GLOBAL ISSUES IN LANGUAGE EDUCATION - Muhayyo Usmonjonovna, Ziyayeva; Jasmina Bakhodir Kizi, Abdullayeva (Journal of Higher Education and Academic Advancement, 2025)
Objective: This paper aims to explore the global challenges and opportunities in language education, focusing on issues such as linguistic diversity, the dominance of global languages, language policy, and the role of technology in shaping educational practices. Methods: The study uses a qualitative approach, analyzing existing literature and case studies on language education in the context of globalization. It examines the impact of these challenges on language teaching practices and policies, as well as the strategies being implemented worldwide to address them. Results: The paper identifies key issues affecting language education, including the threat to linguistic diversity, the prevalence of dominant global languages, and the disparities in language education systems. It also emphasizes the increasing role of technology in both facilitating and complicating language learning and teaching. Novelty: This study presents an innovative framework for addressing the global language education challenges by proposing solutions that promote inclusivity and cultural respect, while ensuring effective communication in a globalized world. The paper highlights the necessity for policy reforms and technological integration to enhance language education systems across diverse cultural contexts.